Development of antibacterial activity and corrosion resistance properties of electrodeposition of mineralized hydroxyapatite coated on titanium alloy for biomedical applications. (2017) - Chozhanathmisra, M.; Murugan, N.; Karthikeyan, P.; Sathishkumar, S.; Anbarasu, G.; Rajavel, R.
Abstract: Titanium and its alloy are potential biocompatible implant materials, due to their imposing biological properties. Hydroxyapatite [Ca10 (PO4)6 (OH)2, HAP], is a principal inorganic constituent of bone, teeth and it is the most suitable nontoxic biocompatible material. Halloysite nanotubes (HNTs) are a type of natural alumino-silicate clay mineral. To improve the anticorrosion protection properties of HNT, it is deposited on Titanium alloy. The Halloysite Nanotube-Cerium substituted Hydroxyapatite (HNT-Ce-HAP) composite was electrodeposited on Ti alloy using the electro deposition process as a bioactive coating with improved antibacterial activity and anti-corrosion stability in simulated body fluid. The formation of HNT-mHAP composite coating was characterization using FT-IR, X-ray diffraction (XRD), Contact angle, (SEM-EDX) scanning electron microscopy. The antibacterial activity of the as-coated HNT-Ce-HAP particles was evaluated against two pathogen bacterial strains. The HNT-mHAP composite coated Ti6Al4V was analyzed towards human osteoblast (HOS MC3T3-E1 cells) cells using MTT assay. Thus, the as- coated HNT-Ce-HAP composite serves as a better candidate for biomedical applications with good anticorrosion, antibacterial propertie s and with bone bonding ability.